Endogenous and exogenous: Debating the historiography of the industrial revolution and the great divergence - Stefano Agnoletto (Essays in Economic & Business History (EEBH), 2023)
The interpretation of the reasons for the successes and delays in the race for industrialization is still a fundamental issue in the historiographical debate. In particular, the discussion about the "economic success" of the space commonly called the West (that practically means North America, Europe, Japan and Australia/New Zealand) is certainly lively, and its enormous theoretical impact is evident. This article focuses on three different issues: the role played by exogenous factors and endogenous factors in the historiography on different case studies and paths of industrialization; Eurocentrism/ethnocentrism in the approaches to the history of industrialization; and the debate on the roots of the supposed "victory" of the Western (or Euro-American) model. Although the debate is still open, this article shows that in recent decades a new approach on the history of industrialization has emerged and is gaining some hegemony: the need to consider not only endogenous readings of individual cases, but also to insert them into global contexts of relationships.
Keywords: N00; N01; N10; 330; Industrialization; Industrial Revolution; Great Divergence; Eurocentrism